Leadership in Action: Conversation Piece: Using Dialogue as a Tool for Better Leadership - McGuire, John; Palus, Charles (Center for Creative Leadership, 2003)
In times of chaos and complexity, organizations become increasingly fragmented. One way to introduce connection, awareness and appreciation of similarities and differences, and cultivation of shared understandings to the leadership of organizations is through dialogue. Here are some principles that groups can follow in using dialogue to help them steer their way through new and uncertain environments.